Evaluasi Kebijakan Pelimpahan sebagian Kewenangan Bupati kepada Camat di Kecamatan Sagala Herang Kabupaten Subang Tahun 2015 - Suparman, Nanang (Jurnal Politik Indonesia: Indonesian Political Science Review, 2017)
The effort to encourage more subdistrict optimal roles in comunity service by giving authority in the field of licensing as one part delegating authority (Law No.23 of 2014). Subang regency has been implementing this delegating authority since 2012. Licensing services in subdistrict in addition to saving time and costs, can contribute to the PAD, therefore in this study tries to analysis the result of evaluation of the implementation of policy delegating authority in 2015 with a frame of thought on two aspects i.e.what effort have been made and obstacles encountered.This research uses descriptive qualitative approach method, technique of collecting data through observation, documentation analysis and in-dept interview.The results showed that the evaluation to measure the optimalization of delegation of Bupati authority in licensings aspect to Camat can not achieve the goals of policy formulation, it is influenced by factors not yet the existence of the innovation and creativity of public service, havet yet been able to create legal certainty, and havet been able to efficiently utilize the authority assigned because sub-district Sagala Herang havet been able to set up the necessary administrative devises includes a special apparatus resources to handle the licensing authority.